Bioorthogonal Chemistry at Radboud University: Past, Present and Future - Rutjes, Floris P. J. T.; Bonger, Kimberly M.; Neumann, Kevin (Synlett, 2024)
Over the past two decades, bioorthogonal chemistry has profoundly impacted various chemistry-related fields, including chemical biology and drug delivery. This transformative progress stems from collaborative efforts involving chemists and biologists, underscoring the importance of interdisciplinary research. In this Account, we present the developments in bioorthogonal chemistry within our Institute for Molecules and Materials at Radboud University. The chemistry disclosed here spans from strained alkynes and alkenes to drug release and bioconjugation strategies, mirroring the extensive scope provided by bioorthogonal chemistry. By reflecting on the chemistry originating at Radboud University, this Account emphasizes that teamwork is essential for driving significant progress in bioorthogonal chemistry.1 Introduction2 Providing BCN as a Robust Bioorthogonal Tool for Chemical Biology and Beyond3 Towards Readily Available Click-to-Release trans-Cyclooctenes4 Giving Molecules Guidance5 Next Generation of Bioconjugation Strategies: Dynamic Click Chemistry6 Conclusions
Keywords: bioorthogonal chemistry; chemical biology; strained alkynes; tetrazines; drug activation